2014
DOI: 10.3390/antiox3010144
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols, Berries, and Age-Related Bone Loss: A Review Based on Human, Animal, and Cell Studies

Abstract: Bone loss during aging has become an increasing public health concern as average life expectancy has increased. One of the most prevalent forms of age-related bone disease today is osteoporosis in which the body slows down bone formation and existing bone is increasingly being resorbed by the body to maintain the calcium balance. Some causes of this bone loss can be attributed to dysregulation of osteoblast and osteoclast activity mediated by increased oxidative stress through the aging process. Due to certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 74 publications
2
56
1
1
Order By: Relevance
“…These compounds have been reported to be present in various organs of rats, including target organs for Cd, such as kidneys and liver [37]; however, their penetration into the bone tissue has not been investigated, but it cannot be excluded. The available data indicating that consumption of polyphenols improves bone turnover and BMD in both human [21] and experimental animals [16,23] confirm the possibility of the direct impact of these compounds on bone status.…”
Section: Figmentioning
confidence: 63%
See 1 more Smart Citation
“…These compounds have been reported to be present in various organs of rats, including target organs for Cd, such as kidneys and liver [37]; however, their penetration into the bone tissue has not been investigated, but it cannot be excluded. The available data indicating that consumption of polyphenols improves bone turnover and BMD in both human [21] and experimental animals [16,23] confirm the possibility of the direct impact of these compounds on bone status.…”
Section: Figmentioning
confidence: 63%
“…Elliott; Rosaceae]. Nowadays, the consumption of aronia berries is widely recommended as one of the most abundant sources of compounds having a beneficial influence on the organism, and the richest source among plant materials of anthocyanins, which are characterized by strong antioxidative properties [13,14,[18][19][20][21]. Data provided by Kowalczyk et al [15] and our recent findings [6,22,23] seem to indicate that the consumption of chokeberries and their products may prevent Cd accumulation in the body and its toxic action.…”
mentioning
confidence: 99%
“…Berries contain abundant anthocyanins and have been recognized as valuable sources of natural medicines and dietary supplements (29,32). Various studies have demonstrated that berry intake may increase antioxidant status and reduce inflammatory biomarker levels in vivo (29). Based on these findings, our group hypothesized that berry consumption may be helpful in alleviating bone resorption and bone density loss following menopause.…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, Welch et al (31) suggested an anti-osteoporotic effect of anthocyanins in a cohort study of twins, in which the differences between the highest and lowest fifths of anthocyanin intake were associated with a 3.4% higher BMD at the spine and a 3.1% higher BMD at the hip. Berries contain abundant anthocyanins and have been recognized as valuable sources of natural medicines and dietary supplements (29,32). Various studies have demonstrated that berry intake may increase antioxidant status and reduce inflammatory biomarker levels in vivo (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation